Effect of Storage Conditions on Germinability of Himalayan Cedar (Cedrus deodara Roxb., G. Don) Seeds - Kumar, Raj; Singh, Charan; Malik, Saira; Ali, Aasif; Nayital, R. K. (Indian Forester, 2011)
Germinability of seeds of Cedrus deodara Roxb. G. Don was studied under different storage conditions in the laboratory. Seeds were stored at four different temperature namely, room temperature (T1), 5±1°C (T2), 0±1°C (T3), -5±1°C (T4) and in three different container viz.; poly bag (C1), canvas bag (C2) and plastic container (C3). Observation on germination parameters were observed at bimonthly for storage duration of ten month. The results revealed that the temperature -5±1°C (T4) performed better with highest mean value for all germination parameters i.e. germination (71.18%), Germinative capacity (79.40%), Germinative energy (46.33%) and Germination value (11.36%) after ten months of storage. It was also observed that plastic container (C3) performed better with highest mean value for all germination parameters i.e. germination (67.63%), Germinative capacity (76.92%), Germinative energy (43.65%) and Germination value (10.45%)] after ten months of storage.